Size and layout optimization of truss structures with dynamic constraints using the interactive fuzzy search algorithm. Issue 3 (4th March 2021) - Mortazavi, Ali
Abstract : Optimizing truss structures considering natural frequency constraints can fundamentally enhance their dynamic behaviour under transient loadings. In this regard, the current investigation assesses the search capability of the interactive fuzzy search algorithm (IFSA) in solving this class of problem. Since the natural frequencies are very sensitive to configuration changes in the system, throughout the optimization process the algorithm should be able to adaptively shift its search behaviour. To meet this aim, the IFSA utilizes two nine-rule fuzzy modules which permanently monitor the optimization process and try to balance the exploration and exploitation search behaviours of the algorithm. Then, the search capability of the proposed method is tested on five structural benchmark problems. The numeric results reveal that the IFSA, by systematically reducing the number of ineffective iterations, considerably decreases the required computational cost. In addition, considering solution accuracy and process stability, IFSA provides promising results in solving structural optimization problems.